Synthesis and Purification of N3‐Methylcytidine (m3C) Modified RNA Oligonucleotides. Issue 11 (18th November 2021) - Mathivanan, Johnsi; Du, Jinxi; Mao, Song; Zheng, Ya Ying; Sheng, Jia
Abstract: This protocol describes a step‐by‐step chemical synthesis approach to prepare N 3 ‐methylcytidine (m 3 C) and its phosphoramidite. The method for synthesizing m 3 C starts from commercially available cytidine, and proceeds via N 3 ‐methylation in the presence of MeI, which generates the N 3 ‐methylcytidine (m 3 C) nucleoside, followed by the installation of several protecting groups at sites that include the 5 ' ‐hydroxyl group (4, 4 ' ‐dimethoxytrityl protection), the 4‐amino group (benzoyl protection), and the 2 ' ‐hydroxyl group ( tert ‐butyldimethylsilyl, TBDMS, protection). Standard phosphoramidite chemistry is applied to prepare the final m 3 C phosphoramidite for solid‐phase synthesis of a series of RNA oligonucleotides. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of N 3 ‐methylcytidine (m 3 C) and its phosphoramidite Basic Protocol 2 : Automated synthesis of m 3 C modified RNA oligonucleotides